Mechanisms behind distracted driving behavior: The role of age and executive function in the engagement of distracted driving. (January 2017) - Pope, Caitlin Northcutt; Bell, Tyler Reed; Stavrinos, Despina
Highlights: Engagement in distracted driving was evident across the lifespan, including ages 65 and older. Middle-aged adults engaged in distracted driving behaviors at a frequency similar to young adults. The effect of age on distracted driving behaviors was partially mediated by executive difficulty. Age and executive difficulty uniquely predicted the frequency to engage in distracted driving. Abstract: Performing secondary tasks, such as texting while driving, is associated with an increased risk of motor vehicle collisions (MVCs). While cognitive processes, such as executive function, are involved in driving, little is known about the relationship between executive control and willingness to engage in distracted driving. This study investigated the relationship between age, behavioral manifestations of executive function, and self-reported distracted driving behaviors. Executive difficulty (assessed with the BRIEF-A) as well as demographics (age and gender) was considered as possible predictors of engagement in distracted driving behaviors. Fifty-nine young, middle, and older adults self-reported executive difficulty and weekly engagement in distracted driving behaviors. Results revealed that while partially accounted for by age, global executive difficulty was uniquely related to engagement in distracted driving behaviors. Older age was associated with fewer weekly self-reported distracted driving behaviors while higher self-reported executive difficulty was associated with more frequent weekly engagement in distracted behavior. No significant differences were found between young and middle-aged adults on distracted driving behaviors. Findings conclude that distracted driving is a ubiquitous phenomenon evident in drivers of all ages. Possible mechanisms underlying distracted driving behavior could potentially be related to deficits in executive function.